Mechanical behaviour analysis of cemented tailings rock backfill materials: An insight from mesoscale modelling coupled with damage plasticity model - Chaoyi Yang; Hang Lin; Rugao Gao; Zhengrong Li; Dengjun Gan; Mingwu Liu; Qifan Ren (Case Studies in Construction Materials)
Cemented tailings rock backfill (CTRB) is a promising material for recycling mining solid waste and ensuring the stability of underground stopes. However, a comprehensive understanding of the fracture behaviour of CTRB remains limited. This study developed a two-dimensional mesoscale model of CTRB utilizing the concrete damage plasticity material model to simulate the behaviour of cemented tailings backfill (CTB). An experimental program was conducted to determine the mechanical parameters and mesostructure of CTB, as well as the mechanical response of CTRB. The experimental results validated the feasibility of the mesoscale modelling approach and confirmed its consistency with numerical predictions. The study investigated the effects of mix design variables, including waste rock content (WRC), cement-to-tailing ratio of CTB, and waste rock gradation, on damage evolution, failure patterns, strength, and elasticity. The potential application in real scenarios is also discussed. The key findings include: (1) incorporating waste rock significantly enhances elasticity but slightly reduces strength; (2) a lower cement-to-tailing ratio leads to compressive damage playing a more critical role in failure patterns; and (3) increasing the maximum particle diameter negatively impacts strength. Lastly, a formula correlating the attributes of meso-components was proposed to predict the elasticity of CTRB.